Counsellor Education for Diversity: Where Do We Go From Here? - Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
This discussion paper examines current perspectives in counsellor education for diversity. Through addressing issues regarding ethnocentrism in counsellor education programs, practise, research, and the evaluation of multicultural competencies, further directions for counsellor education are outlined. Faculty, counsellors-in-training, and community-based practitioners are challenged to examine the ways in which self-awareness, knowledge, and skills can be applied in the delivery of culturally-responsive counselling services.